Bog wyzej--dom dalej : 1939-1949 - Bien, Adam, 1899- (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1991)
The author's autobiographical account of his underground activities in Poland during World War II.
Includes bibliographical references.
Keywords: Bien, Adam, -- 1899-; Political prisoners -- Poland -- Biography; Political prisoners -- Soviet Union -- Biography; World War, 1939-1945 -- Underground movements -- Poland; World War, 1939-1945 -- Personal narratives, Polish; Moscow Trial, Moscow, Russia, 1945.